The impact of a blended web-based learning environment on the perceptions, attitudes, and performance of boys and girls in junior science and senior physics - Chandra, Vinesh (Curtin University, 2004)
In some classrooms, teaching methods have evolved little over the years. Enrolments in subjects like science have progressively declined and the persistent use of traditional teaching methods has often been held responsible for this. In less than a decade, the Internet has emerged as a potential tool to vary classroom routines, however, its use in high school science classrooms is still in its infancy. In this study, Getsmart, a website was developed and implemented in junior science and senior physics classrooms in a blended learning environment in a Queensland State High School. The study had three main objectives amongst others. The first aim was to study the impact of such an environment on students' perceptions. Secondly, the impact of such an environment on students' attitudes towards physics and junior science was studied. Finally, the research sought to investigate the effect of such an environment on their learning outcomes. Getsmart was developed on the principles of cognitive apprenticeship teaching model (Collins, Brown, & Newman, 1989). During the research phase, the website was accessed by students once a week during class time. They also had the option to login in their own time at school (e.g., morning tea, lunchtime, before and after school) and at home. The research was conducted as a case study over two years and during this time, 406 students in junior science and physics participated. Students' perceptions of their learning environment were ascertained through quantitative and qualitative methods. Quantitative data were collected by using a modified version of the Web-based Learning Environment Instrument (WEBLEI) (Chang & Fisher, 2003).Qualitative data on student's attitudes were gathered through emails and Written surveys. An Attitude to Science survey was developed to determine students' attitudes towards their subjects. Qualitative data were also gathered through written surveys. The impact of such an environment on students' learning outcomes was determined through the analysis of their exam results achieved before and after experiencing web-based learning. Their results were also compared with the results of similar cohorts in previous years. Amongst other findings, it was found that the modified version of the WEBLEI was a valid and reliable instrument for use in junior science and physics classes. The study also established that students had positive perceptions of a blended web-based learning environment and that such an approach had a positive influence on students' attitudes towards their subjects. The study also found that web-based learning improved their performance across various performance domains of junior science and senior physics assessments.